Technology Entrepreneurship Project (ENT 600) : Reebok Company / Janet Linda Pagang - Pagang, Janet Linda (2021)
This assignment is about a Reebok Company which manufactures the various type of product that we interested in. As a student of UiTM Perlis, it is our part and duty to undergo a case study project. Therefore, I would like to know and identify the problem of Reebok’s products which is I interested with sport water bottle. First of all, all the information been collected through the primary and secondary sources. The goal of the case study is to figure the problem that faced by Reebok products, organizational structure, product and service that offer by Reebok Company. In this case study, I used SWOT analysis which is strength, weakness, opportunity and threats to analyse the product of Reebok. Other than that, I do some research for Reebok’s product, which is a part of their equipment that is sport water bottle. There are several problems that I found include problem with delivery, limited in colours and having a bad reviews and feedback from customers. I will explain more detail regarding the problems I found and provide some findings and discussion to seek for alternatives solutions to the problems.